Islamic Eco-Theology: Religious Narratives in the Climate Crisis in Indonesia - Mansur Hidayat (KURAS Institute, 2023)
This article delves into the adaptation of Islamic eco-theology as an analytical lens to dissect religious narratives surrounding the climate crisis in Indonesia. With insights derived from a spectrum of interpretations and diverse affiliations, this eco-theology provides a foundation for varied understandings and reactions to environmental challenges. The study is designed to synthesize theory and hermeneutics within a critical-qualitative framework, exploring the interplay between theology and ecology. Ecological and theological behavioural theories are employed to elucidate the data. The findings reveal two main aspects: Firstly, the representation of eco-theology in Islam has undergone a metamorphosis, expanding from its role as a catalyst for uniform responses to environmental issues to a factor enriching the dynamics of understanding and response. Secondly, although the network of Islamic eco-theology influences the perspectives of the Muslim community, its capacity to reach a broader spectrum is still limited. The study underscores that Islamic eco-theology plays a pivotal role as a subsystem in navigating responses to environmental crises, particularly in responding to the climate crisis increasingly integrated within the framework of religious thought and practice in Indonesia.